Reliability of an Instrumented Pressure Walkway for Measuring Walking and Running Characteristics in Young, Athletic Individuals - Alyx Jorgensen; Matthew McManigal; Austin Post; David Werner; Christopher Wichman; Matthew Tao; Elizabeth Wellsandt (North American Sports Medicine Institute, 2024)
# Background Spatiotemporal parameters of gait are useful for identifying pathological gait patterns and presence of impairments. Reliability of the pressure-sensitive Zeno^TM^ Walkway has not been established in young, active individuals without impairments, and no studies to this point have included running. # Purpose The purposes of this study were to 1) determine if up to two additional trials of walking and running on the Zeno^TM^ Walkway are needed to produce consistent measurements of spatiotemporal variables, and 2) establish test-retest reliability and minimal detectable change (MDC) values for common spatiotemporal variables measured during walking and running. # Study Design Cross-Sectional Laboratory Study # Methods Individuals (n=38) in this cross-sectional study walked and ran at self-selected comfortable speed on a pressure-sensitive Zeno^TM^ Walkway. Twenty-one participants returned for follow-up testing between one and 14 days later. Intraclass correlation coefficients (ICCs) were used to assess reliability of spatiotemporal variable means using three, four, or five passes over the Zeno^TM^ Walkway and to assess test-retest reliability of spatiotemporal variables across sessions. # Results All variables showed excellent reliability (ICC \> 0.995) for walking and running when measured using three, four, or five passes. Additionally, all variables demonstrated moderate to excellent test-retest reliability during walking (ICC: 0.732-0.982) and running (ICC: 0.679-0.985). # Conclusion This study establishes a reliable measurement protocol of three one-way passes when using the Zeno^TM^ Walkway for walking or running analysis. This is the first study to establish reliability of the Zeno^TM^ Walkway during running and in young, active individuals without neuromusculoskeletal pathology. # Level of Evidence 3b